Controlled Constitutionalism and the Decline of Institutional Independence in Indonesian Constitutional Law - Hadi Iskandar; Yusrizal Hasbi; Muhamad Sadi Is (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
The weakening of institutional independence has become a significant challenge for constitutional democracies, particularly in states experiencing democratic decline without formal constitutional rupture. Existing theories, including abusive constitutionalism, constitutional capture, and executive aggrandizement, primarily explain democratic erosion through constitutional amendments, direct institutional takeovers, or overt expansions of executive authority. These approaches provide limited explanatory power for cases in which constitutional structures remain formally intact while institutional autonomy is gradually constrained through ordinary legal mechanisms. This article addresses that gap by introducing the concept of controlled constitutionalism to explain constitutional developments in Indonesia between 2014 and 2025. Using a normative legal research method with statutory, conceptual, and institutional approaches, the study combines quantitative indicators of the rule of law, institutional integrity, and public trust with qualitative analysis of legislative reforms, judicial decisions, and institutional restructuring involving the Constitutional Court, Supreme Court, Corruption Eradication Commission, Judicial Commission, and other oversight bodies. The findings reveal that institutional independence has eroded through a cumulative process of executive consolidation, legal institutionalization, judicial legitimation, and functional subordination. Rather than dismantling constitutional institutions, these mechanisms reconfigure them into a system of hierarchical governance that preserves formal legality while reducing substantive autonomy. The article argues that controlled constitutionalism constitutes a distinct form of constitutional regression in which law serves as a mechanism of institutional dependence rather than a safeguard against power concentration. This framework offers a new perspective for understanding democratic erosion under conditions of formal constitutional continuity and contributes to broader debates on democratic backsliding in emerging democracies.